2018
DOI: 10.1108/mrr-04-2017-0123
|View full text |Cite
|
Sign up to set email alerts
|

Timeline of engagement research and future research directions

Abstract: Purpose Studies suggest that engagement is related with organizationally desired outcomes, including performance, productivity, profitability, employee retention, organization citizenship behavior and employee well-being. Despite its practical relevance in the workplace, the concept of engagement has been theoretically dispersed. Therefore, this study aims to present a conceptual review of engagement studies leading to the development of a nomological framework and an evolution timeline for the concept. Desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 102 publications
0
7
0
Order By: Relevance
“…Despite the popularity of work engagement and the evidence that work engagement is positively associated with organizationally desired outcomes (Kunte and Rungruang, 2018), It also tends to support the view that focus should be shifted from job resources to personal resources as they provide a sustainable and self-sustaining approach toward increasing work engagement. This finding also complies with the spillover hypothesis, which advocates that experiences from one life domain (such as predisposition to overall satisfaction with life in the current study) influences the experiences in other life domains (such as work engagement) (Judge et al, 2001).…”
Section: Theoretical Contributionmentioning
confidence: 99%
“…Despite the popularity of work engagement and the evidence that work engagement is positively associated with organizationally desired outcomes (Kunte and Rungruang, 2018), It also tends to support the view that focus should be shifted from job resources to personal resources as they provide a sustainable and self-sustaining approach toward increasing work engagement. This finding also complies with the spillover hypothesis, which advocates that experiences from one life domain (such as predisposition to overall satisfaction with life in the current study) influences the experiences in other life domains (such as work engagement) (Judge et al, 2001).…”
Section: Theoretical Contributionmentioning
confidence: 99%
“…The third objective is to introduce three new independent variables (supportive workspace design, vision alignment and cultivation of high-quality leader-member relationships) to Grawitch et al's (2006) five-factor model of healthy workplace practices, and test whether any of these new variables help to explain incremental variance beyond that of the original five factors for any of the above-noted dependent variables (job satisfaction, overall life satisfaction and work engagement). In addition to meeting the aforementioned calls by Grawitch et al (2007) for research that examines different outcome variables and uses a different sample, the present study also addresses Kunte and Rungruang's (2018) call for more research on the determinants of work engagement, and contributes to a fuller understanding of the antecedents of job satisfaction and overall life satisfaction as well.…”
Section: Research Objectivesmentioning
confidence: 88%
“…The newer model of healthy workplace practices offered in this paper better predicts outcomes associated with healthy workplaces, and emphasizes the importance of being attentive to the workspace design, promoting the cultivation of high-quality manageremployee relationships, and ensuring that the organization's vision aligns with the values and preferences of employees. Such research answers Kunte and Rungruang's (2018) call for further studies on the determinants of work engagement, and contributes to a fuller understanding of the antecedents of job satisfaction and overall life satisfaction. Future research should examine how the eight workplace practices identified in the present study affect other important outcomes (e.g.…”
Section: Research Implicationsmentioning
confidence: 92%
“…The findings from this study parallel the research-based assertion that employees were more likely to be engaged when they have a clear role and expectations understanding. Studies have supported this definition by indicating individuals who identify with their work are less likely to be impacted by quitting and absenteeism (Bakker and Demerouti, 2008;Kunte and Rungruang, 2018;Shuck et al, 2014). Employees' engagement in their work has a positive influence on knowledge creation, customer loyalty, individual performance and financial returns (Azim et al, 2019;.…”
Section: Discussionmentioning
confidence: 99%